1987
DOI: 10.1007/bf01403212
|View full text |Cite
|
Sign up to set email alerts
|

Highly concentrated ceramic binder suspensions. Dispersion medium, stabilization, and binding properties

Abstract: In the previous series of papers on the highly concentrated ceramic binder suspensions (HCBS), it was shown that a number of technological principles must be followed directly during the process of wet milling for producing HCBS: it is necessary to maintain high concentration and high temperature [i] and optimum degree of dispersion, granulometric distribution, dilution of HCBS, and dissolution of the solid phase [2]. The properties of HCBS obtained by following the aforementioned principles can be significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
20
0

Year Published

1988
1988
2007
2007

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 4 publications
0
20
0
Order By: Relevance
“…In order to obtain additional and important data on the characteristics of the dispersion composition of HCBS it was suggested in [31] to single out two conventional levels (ranges) of dispersity, i.e., (I) that of particles of solid phase with a size ranging from 0.2 -0.5 mm to a maximum value of 30 -100 mm and (II) particles with a size below 0.2 mm. The latter range can be conventionally treated as that of nanoparticles.…”
Section: Dispersion Medium Of Hcbs As a Composite Nanodisperse Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to obtain additional and important data on the characteristics of the dispersion composition of HCBS it was suggested in [31] to single out two conventional levels (ranges) of dispersity, i.e., (I) that of particles of solid phase with a size ranging from 0.2 -0.5 mm to a maximum value of 30 -100 mm and (II) particles with a size below 0.2 mm. The latter range can be conventionally treated as that of nanoparticles.…”
Section: Dispersion Medium Of Hcbs As a Composite Nanodisperse Systemmentioning
confidence: 99%
“…In [31] we used an ultracentrifuge with rotor speed of 18,000 rpm rotated for 15 min for separating the colloidal component. We studied samples of a dispersion medium obtained by long-term settling of repeatedly diluted suspensions.…”
Section: Dispersion Medium Of Hcbs As a Composite Nanodisperse Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…According to us, as was shown earlier [5], the main distinguishing feature of the cementfree refractory binders is the methodological separation of the solid phase of the binder system into two levels of dispersion, viz., i) the particles having a size ranging from 0.2-0.5 up to i00 pm that form a mineralogical microfilier having an active surface; and 2) the particles having a size below 0.2-0.5 pm that are classified as the colloidal component. These two levels of dispersion play different roles in the process of structure evolution during dehydration and determine the other characteristic properties of the new group of binders.…”
mentioning
confidence: 95%
“…Chemical binders include molecular-or colloidal-dispersed solutions and inorganic sols that are characterized by their polymerization nature of hardening (liquid glass, phosphate binders, oxychloride solutions silica-and aluminasols etc.). The refractory concretes obtained using the aforementioned binders are characterized by a high degree of heterogeneity with respect to chemical and mineralogical composition because of which the service characteristics of these materials are most adversely affected.As was indicated in our previous papers on this subject [3,4], the main methods of solving the aforementioned problem include changing the material composition of the binder by replacing a large portion of the cement with an ultrafine (highly dispersed) mineralogical component and obtaining homogeneous systems (highly concentrated binder systems HCBS) whose dispersing medium consists of a sol or a gel synthesized during the preparation of HCBS and dispersed phase consists of an activated microfiller of the same refractory composition (system).Our previous studies [5,6] demonstrated for the first time that the content Ccc of the colloidal component, i.e., the content of the ultrafine (30-40 run) particles "generated' during wet milling and stabilization of HCBS forms the main parameter determining their rheoiogical, technological, and binding properties. Figure 1 shows a typical example of the effect of the relative (with respect to the total mass of the solid phase of HCBS) content of the colloidal component Ccc (in the given case, its quantity was controlled by the duration of stabilization by mechanical agitation) on the characteristics of HCBS of the muilite-corundum system.…”
mentioning
confidence: 99%